The meaning of the letter of Aristeas: in light of Biblical interpretation and grammatical tradition, and with reference to its historical context - Matusova, Ekaterina (Forschungen zur Religion und Literatur des Alten und Neuen Testaments, 2015)
Cover -- Title Page -- Copyright -- Tables of Contents -- Body -- Introduction -- Chapter 1: The biblical paradigm, or the Letter of Aristeas as Rewritten Scripture -- 1.1 The liberation of Jewish slaves in connection with the translation as elaboration on Deut 30:1-3 -- 1.2 The description of the Promised Land (Let. Aris. 83-120): elaboration on Deut 30:3-5 -- 1.3 The allegorical interpretation of the Law and the Symposium (Let. Aris. 128-293): another case of harmonization -- 1.4 Conclusions: The rationale and methodology of the composition -- 1.5 Conclusions: The message of the "biblical paradigm" and its Sitz im Leben -- Chapter 2: Account of the translation, or the grammatical paradigm -- 2.1 Introduction -- 2.2 Thesis of Kahle - Van der Kooij -- 2.3 The Aristotelian background to the narrative in Let. Aris. 30-2 -- 2.4 The 72 and the anecdote about the recension of Homer in the scholia to Dionysius Thrax -- 2.4.1 The 72 -- 2.5 Let. Aris. 301-11 and the six (or four) steps of grammar -- 2.6 Let. Aris. 310-11 and literary criticism -- 2.7 Thesis of analogy with Homer -- 2.8 The meaning of grammatical terminology: interim conclusions -- 2.9 Account of the correction in the context of the early history of the LXX -- Chapter 3: The interactive meaning of the paradigms, or historical implications of the narrative -- 3.1 The LXX as ἱερὸς λόγος in the Letter of Aristeas -- 3.2 Beyond the Letter of Aristeas: General historical context -- 3.2.1 Words and terms used in the Greek and Graeco-Jewish sources to describe the Jewish cult: Temples -- 3.2.2 Words and terms referring to the Jewish cult: Priests -- 3.2.3 Words and terms referring to the Jewish cult: Thiasus -- 3.2.4 The Jewish cult as a mystery cult -- 3.2.5 Interim conclusions -- 3.3 Oriental religious communities in the Hellenistic states: Rules of integration